Task offloading concept using cloud simulations in mobile computing. (10th May 2021) - Goundar, Sam; Bhardwaj, Akashdeep; Chand, Shalmendra
The seamless execution of application is important in mobile cloud applications. The limited processing power of mobile devices with insufficient resources to handle computational processing of complex applications is compared to the cloud infrastructure, which can handle multiple tasks simultaneously due to its multiple virtual machines and hosts. By simulating the concept of task offloading, application partitioning is handled to accommodate heavy computing requirements for mobile devices with insufficient resources. This research paper proposes the usage of CloudSim to simulate cloud architecture and the task-offloading concept using cloudlets. The authors present various application offloading architecture, cloudlet architecture, security challenges and issues in the realm of mobile cloud computing.